Local Self-Governance in Antiquity and in the Global South Theoretical and Empirical Insights from an Interdisciplinary Perspective - Krüger, Dominique; Mohamad-Klotzbach, Christoph; Pfeilschifter, Rene (De Gruyter, 2023)
The nucleus of society is situated at the local level: in the village, the neighborhood, the city district. This is where a community first develops collective rules that are intended to ensure its continued existence. The contributors look at such configurations in geographical areas and time periods that lie outside of the modern Western world with its particular development of society and statehood: in Antiquity and in the Global South of the present. Here states tend to be weak, with obvious challenges and opportunities for local communities. How does governance in this context work? Scholars from various disciplines (Classics, Theology, Political Science, Sociology, Social Anthropology, Human Geography, Sinology) analyze different kinds of local arrangements in case studies, and they do so with a comparative approach. The sixteen papers examine the scope and spatial contingency of forms of self-governance its legitimization and the collective identity of the groups behind them the relations to different levels of state governance as well as to other local groups. Overall, this volume makes an interdisciplinary contribution to a better understanding of fundamental elements of local governance and statehood.